2004
DOI: 10.1108/01443570410541984
|View full text |Cite
|
Sign up to set email alerts
|

Quality management practices in the purchasing function

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 77 publications
1
38
1
1
Order By: Relevance
“…However, not all TQM implementers have executed their TQM successfully. These contradicts findings were reported by other researchers Sanchez-Rodriguez & Martinez-Lorente, 2004;Sohal & Terziovski, 2000;Witcher, 1994). In a review paper, Sila and Ebrahimpour (2002) concluded that previous studies on the relationship between TQM and performance had revealed inconsistencies and sometimes produced conflicting results.…”
Section: Introductioncontrasting
confidence: 47%
“…However, not all TQM implementers have executed their TQM successfully. These contradicts findings were reported by other researchers Sanchez-Rodriguez & Martinez-Lorente, 2004;Sohal & Terziovski, 2000;Witcher, 1994). In a review paper, Sila and Ebrahimpour (2002) concluded that previous studies on the relationship between TQM and performance had revealed inconsistencies and sometimes produced conflicting results.…”
Section: Introductioncontrasting
confidence: 47%
“…A number of studies have actually employed SERVQUAL in order to measure internal service quality (Boshoff and Mels, 1995;Frost and Kumar, 2001;Kang et al, 2002;Sánchez-Rodríguez and Martínez-Lorente, 2004;White and Rudall, 1999). Other researchers regard the measurement of internal service quality as being too complex a task to implement by merely adapting existing instruments from external customer research (Finn et al, 1996;Marshall et al, 1998;Vandermerwe and Gildert, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It thus expands and extends academic knowledge developed by previous studies (Hemsworth et al, 2005(Hemsworth et al, , 2008Sánchez-Rodríguez and Martínez-Lorente, 2004) which were in part presented in this journal. Furthermore, it provides managerial insights for the management of externally sourced business services.…”
Section: Resultsmentioning
confidence: 73%